Collaborative Governance Program Sinau Bareng Untuk Mengatasi Kekerasan Kepada Anak Di Kelurahan Kandangan Surabaya - Nurul Aulia Ridwan; Supri Hartono (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Violence that occurs against children in the family in Indonesian Government Regulation Number 78 of 2021 concerning Special Protection of Children is a child who is threatened physically and non-physically due to acts of violence, is treated wrongly or inappropriately in the family or immediate social environment, so that his or her basic needs are not met properly. normal both physically, spiritually and socially. So in implementing Puspaga at the RW Hall, DP3APPKB Surabaya also collaborated with the Surabaya Education Office (Dispendik). One of them is through the Sinau program at Balai RW. The Puspaga at RW Hall can also be a space for children to vent. This research uses a qualitative approach, with a type of descriptive research where the problem formulation triggers researchers to explore social situations in a comprehensive and in-depth manner. According to (Sugiyono, 2017) descriptive research is a type of research that aims to present a complete picture of social conditions. This research was carried out in the Kandangan Village area, Benowo District, Surabaya City. The purpose of this research is to find out about the Sinau Bareng program in overcoming children's problems in Kandangan Village. This research uses the Collaboration theory from Ansell and Gash that there are four (4) main components in collaboration; Face-to-face dialogue, building trust, commitment to the process, sharing understanding.